Increased Strength of Sintered Body Hydroxyapatite (HA) with the Addition of Silica as a Reinforcing Material - Hidayat, Rahmat; Ade Indra,; Subardi, (ReTII, 2022)
Sintered body hydroxyapatite (HA) is in the form of pellets with the addition of silica as a reinforcing material. The using the average particle size of HA powder is 112.7 μm and the average particle size of silica powder is 11.11 μm. It has been prepared with a HA-Silica ratio of 97:3, 94:6, 88:12, 85:15, 82:18, % by weight. Each ratio of HA-Silica was added with liquid polyvinyl alcohol (PVA) as a binder (added ethanol as a solvent). The mixture was dried at room temperature for 48 hours to remove the ethanol. The lumps of the mixture were mashed again using a rotary drum for 2 hours with a ceramic ball inside. Green body is made by uniaxial pressing method at a pressure of 100 MPa. The sintering process was carried out with a temperature of 1200℃, holding time 2 hours, heating rate 3℃/minute, cooling rate 3℃/minute until temperature 800℃ and 5℃/minute until temperature 300℃. The physical characteristics of HA sintered body were determined by linear shrinkage, density and relative density testing and compressive strength testing to determine the mechanical properties. The results of the linear shrinkage test were indicated by a weight loss of 4.62% and an increase in diameter shrinkage of 7.68%. The increased product density was indicated by the results of the density and relative density test, which increased in the value of density 25.9% and relative density of 0.73%. Changes in physical properties are indicated by the increase in the compressive strength test value of 73.93 MPa.